Regulatory protein SrpA controls phage infection and core cellular processes in Pseudomonas aeruginosa - Jiajia You (Nature Portfolio, 2018)
You et al. show that SrpA, a small protein widely conserved among bacteria, controls core cellular processes in response to phage infection and environmental signals in Pseudomonas aeruginosa, including cell motility, chemotaxis, biofilm formation, and virulence.